LC-MS/MS Method for Simultaneous Quantification of Dexmedetomidine, Dezocine, and Midazolam in Rat Plasma and Its Application to Their Pharmacokinetic Study. (20th May 2018) - Cui, Wenjuan; Liu, Qin; Xiong, Shan; Qiao, Lujun
Abstract : A simple, sensitive, and accurate LC-MS/MS method was established and validated for the simultaneous quantification of dexmedetomidine, dezocine, and midazolam in rat plasma. Chromatographic separation was achieved on a C18 column (50 mm × 2.1 mm, 3  µ m) using a mobile phase composed of water (containing 0.1% formic acid) and acetonitrile. The lower limits of quantification were 0.1, 0.1, and 0.2 ng/mL for dexmedetomidine, dezocine, and midazolam in rat plasma, respectively. The analytes were determined with selected reaction monitoring under positive ionization mode. The intra- and interday precision and accuracy were all within acceptable limits during the entire validation, and the stability of analytes was acceptable under various storage conditions. The validated method was successfully applied in pharmacokinetic studies of dexmedetomidine, dezocine, and midazolam following intravenous injection.